1987
DOI: 10.1093/clinids/9.supplement_5.s620
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Impairment of Macrophage Antimicrobial Activity: Mechanisms and Dependence on the State of Activation

Abstract: Experimental observations indicate that tissue macrophages deployed in great numbers at critical anatomic sites such as the liver, spleen, and lung are major targets for glucocorticoids compromising natural resistanceof the host. Therapeutic concentrations ofglucocorticoids appear to prevent destruction of microorganisms ingested by macrophages without interfering with phagocytosis, phagolysosomal fusion, and/or secretion of reactive oxygen intermediates. These findings indicate that at the cellular level the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 28 publications
(45 reference statements)
2
31
0
1
Order By: Relevance
“…Furthermore, it has been demonstrated that lymphokines, such as IFN-γ, can restore the microbicidal activity of glucocorticoid-suppressed macrophages [22]. Thus, it is conceivable that lymphocytes coexisting with PMs in the peritoneum could counterbalance the suppressive effect of Dex on the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that lymphokines, such as IFN-γ, can restore the microbicidal activity of glucocorticoid-suppressed macrophages [22]. Thus, it is conceivable that lymphocytes coexisting with PMs in the peritoneum could counterbalance the suppressive effect of Dex on the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on the ability of stressors to suppress immunity, and it is now known that factors such as HPA axis-derived glucocorticoid (GC) hormones can suppress important transcription factors, such as NF-B (61). As a result, prolonged elevations of glucocorticoids have been shown to suppress macrophage activity (2,10,21,53).…”
mentioning
confidence: 99%
“…In vitro studies have demonstrated an inhibitory effect of high corticosteroid concentrations on oxygen radical production in human granulocytes [15]. In contrast, dexamethasone treatment has been reported to have no effect on ROS secretion in human blood-derived macrophages [16], but have a stimulatory effect on human monocytes [17]. It has been reported that in vivo corticosterone had no effect on murine peritoneal inflammatory cells [18].…”
mentioning
confidence: 99%